LITERARY EDUCATION IN DIGITAL TRANSFORMATION FOR THE MILLENNIALS GENERATION - Nugrahani, Farida; Widayati, Mukti; Septiari, Wahyu Dini (Prosiding Konferensi Internasional Kesusasteraan, 2025)
The development of digital technology has changed the way millennials interact with information, including in the field of literary education. Digital transformation presents new opportunities for teaching literature through the use of interactive media, digital platforms, and learning applications that encourage student engagement. However, these changes also require educators to adjust their strategies so that literary learning remains relevant, interesting, and capable of fostering aesthetic appreciation amid the rapid flow of digital information. This study aims to analyze the role of digital transformation in literary education for millennials and identify effective learning models in the digital context. The research method used is descriptive qualitative with data collection through literature study, observation of digital media uses, and interviews with educators and students. The results of the study show that the integration of digital technology, such as interactive e-books, online discussion forums, and literacy social media, can increase interest in learning literature and expand access to cross-cultural literary works. In addition, digital-based learning strategies encourage millennials to be more active and creative in interpreting literary works. The implications of this study emphasize the importance of digital literacy training for educators and the development of interactive literary learning platforms so that literary education remains relevant in the era of digital transformation.